PENERAPAN PENDIDIKAN ISLAM BERBASIS MULTIKULTURAL MADRASAH ALIYAH NURUL AS’ADIYAH CALLACCU SENGKANG KABUPATEN WAJO - Aras, Indo Nyalla (Inspiratif Pendidikan, 2018)
The application of multicultural-based Islamic education is the process of fostering and developing human potential so that the purpose of its presence in the world as a servant of Allah is achieved as well as possible, and shows attitudes and gives clear recognition of differences in understanding, ethnicity, race and ethnicity in the midst of society students. The application of multicultural based Islamic education can be seen from several instruments through teaching materials used, activities carried out by students and methods used by educators in the learning process in the classroom. Through the application of multicultural-based Islamic education can create Islamic values and embedded mutual respect and tolerance among fellow students.